2015
DOI: 10.1115/1.4028556
|View full text |Cite
|
Sign up to set email alerts
|

Band-Gap of a Soft Magnetorheological Phononic Crystal

Abstract: This paper presents the wave propagation in a tunable phononic crystal consisting of a porous hyperelastic magnetorheological elastomer (MRE) subjected to an external magnetic field. Finite deformations and magnetic induction influence phononic characteristics of the periodic structure through altering the geometry and material properties of the unit cell. The governing equations for incremental time-harmonic plane wave motions superimposed on a static predeformed media are derived. Analytical and finite eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…For instance, Tipton et al [17] embedded permanent magnets into a cellular, elastic metamaterial and applied an external field to force the system into the collapsed state; it was hypothesized that this experimentally observed capability was scalable and useful as an actuation mechanism for topological change. Bayat and Gordaninejad [18] [19] have recently used multiphysics finite element simulations to study the role of isotropic MRE on these collapsing mechanisms for elastic wave transmission control. In the models, the researchers consider cellular metamaterial composed of isotropic MRE; when acted upon by external magnetic fields, the metamaterials may deform or collapse, and thus adjust the bandgap behavior for elastic waves.…”
Section: Smasis2016-9252mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Tipton et al [17] embedded permanent magnets into a cellular, elastic metamaterial and applied an external field to force the system into the collapsed state; it was hypothesized that this experimentally observed capability was scalable and useful as an actuation mechanism for topological change. Bayat and Gordaninejad [18] [19] have recently used multiphysics finite element simulations to study the role of isotropic MRE on these collapsing mechanisms for elastic wave transmission control. In the models, the researchers consider cellular metamaterial composed of isotropic MRE; when acted upon by external magnetic fields, the metamaterials may deform or collapse, and thus adjust the bandgap behavior for elastic waves.…”
Section: Smasis2016-9252mentioning
confidence: 99%
“…In the models, the researchers consider cellular metamaterial composed of isotropic MRE; when acted upon by external magnetic fields, the metamaterials may deform or collapse, and thus adjust the bandgap behavior for elastic waves. The computational results suggested that wave transmission amplitude and direction could be modified by the non-contact magnetic field [18] [19] To summarize the developments in the state-of-the-art, passive-adaptive elastomeric support systems have usefully leveraged MRE materials for practical properties (and performance) change, although the greatest adaptation possible in these architectures is limited by the energy available to apply external magnetic fields. Also, despite the discoveries regarding cellular elastic metamaterials and recent computational explorations that incorporate MRE, there is no understanding on how anisotropic MRE may govern the properties adaptation of elastic metamaterials and no reported experimental efforts to date that provide a pathway to deliver on the promising opportunities that may be realized via the integration of magnetoelasticity and metamaterials.…”
Section: Smasis2016-9252mentioning
confidence: 99%
“…The active control technology has also been employed to perform the adjustment of the band-gap performance of the periodic structures (Allam et al, 2016; Nouh et al, 2016). In recent years, with the development of smart materials such as the magnetoelastic materials (Bayat and Gordaninejad, 2015; Matar et al, 2012; Schaeffer and Ruzzene, 2015), the dielectric elastomer composites (Bortot et al, 2018), the magnetoelectroelastic materials (Wang and Li, 2009), the electroactive composites (Zhou et al, 2018), and the piezoelectric materials (Piliposian et al, 2012), they have received more and more attention. The vibration reduction of a cantilever beam shunted by the piezoelectric patches was studied and optimized (Ducarne et al, 2012), the optimization was conducted by maximizing the modal electromechanical coupling factor, and the size and laying positions of the piezoelectric sheets were optimized.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a growing interest in using PCs with magnetic materials to tune band gaps [11][12][13][14][15][16][17][18][19][20]. For example, Wang et al have investigated the elastic wave propagation in the magneto-electro-elastic phononic crystals and considered the effects of the piezoelectricity and piezomagnetism on the band structures [12].…”
Section: Introductionmentioning
confidence: 99%
“…After that, a mechanical-magneto-thermal model has been proposed by Zhang et al, and they suggest that the demagnetization effect should not be ignored [17]. Bayat et al have investigated the band structure properties of a soft magnetorheological phononic crystal (PC) [18]. Their studies indicate that large deformations and external magnetic field could transform the location and width of band gaps.…”
Section: Introductionmentioning
confidence: 99%